Analisis Bahasa Anies-Muhaimin pada Tayangan “Usai Putusan MK Anies-Muhaimin Menghormati dan Beri Selamat Ke Prabowo Gibran” di Channel Youtube Kompas TV Sukabumi - Hanif Mutiara Syifa; Ahmad Zamzamy (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In political campaigns, rhetoric plays an important role to attract public attention. The Anies-Muhaimin candidate pair utilised the Youtube social media platform to campaign and discuss with the people through the "DESAK ANIES" and "SLEPET, IMIN" programmes, which aimed to deliver political messages and increase popularity. The programmes include interviews, panel discussions and vlogs. This research uses qualitative methods to understand the dynamics of their political campaigns. The research revealed that the rhetoric of the Anies-Muhaimin pair had a significant impact on public acceptance during the 2024 election campaign. The combination of ethos, logos, and pathos used in their speeches succeeded in creating a space of acceptance and trust that the constitutional process had been completed with the results of the final Constitutional Court decision. The ethos rhetorical technique was also used by Anies to recognise Prabowo's credibility as president-elect. As a result, Anies-Muhaimin's rhetoric was able to create a fair and peaceful democratic atmosphere, and restore the divisions that occurred during the election process, making the community back in harmony and order during the election